Angiogenesis Inhibitors in Personalized Combination Regimens for the Treatment of Advanced Refractory Cancers - Crook, Timothy; Patil, Darshana; Nagarkar, Rajnish; Gaya, Andrew; Plowman, Nicholas; Limaye, Sewanti; Srivastava, Navin; Akolkar, Dadasaheb; Ranade, Anantbhushan; Bhatt, Amit; Datta, Vineet; Bose, Chirantan; et al. (Frontiers in Molecular Medicine, 2021)
ABSTRACT Background Angiogenic factors are commonly activated in solid tumors and present a viable therapeutic target. However, anticancer treatment with angiogenesis inhibitors (AGI) is limited to a few cancers, mostly as monotherapy and not selected based on molecular indications. We aimed to determine whether patient-specific combination regimens with AGI and other anticancer agents when selected based on multi-analyte tumor interrogation (ETA: Encyclopedic Tumor Analysis) can expand the scope of AGIs in advanced refractory solid organ cancers with improved treatment responses. Methods We evaluated treatment outcomes in 60 patients with advanced, refractory solid organ cancers who received ETA-guided combination regimens of AGI with other targeted, endocrine or cytotoxic agents. Radiological evaluation of treatment response was followed by determination of Objective Response Rate (ORR), Disease Control Rate (DCR), Progression Free Survival (PFS) and Overall Survival (OS). Results Among the 60 patients, Partial Response (PR) was observed in 28 cases (46.7%), Stable Disease (SD) was observed in 29 cases (48.3%) and Disease Progression (PD, within 60 days) was observed in 3 cases (5.0%). The ORR was 46.7% and DCR was 95.0%. At the most recent follow, up the median PFS (mPFS) was 5.0 months and median OS (mOS) was 8.9 months. There were no Grade 4 therapy related adverse events or treatment related deaths. Conclusions ETA-guided patient-specific combination regimens with AGI and other anti-neoplastic agents, can yield improved outcomes over AGI monotherapy.